ANALISIS KEBUTUHAN PARKIR PADA KAMPUS UNIVERSITAS ATMA JAYA MAKASSAR - Rumengan, Yuanda (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Parking facility is defined as the location where the vehicle stops temporarily not to conduct activities in a time series. The need for a parking space at public places such as campus has been an absolute thing. This study aims to determine the need for parking space at Atma Jaya University Makassar. The study was conducted by using the data collection from the parking vehiclesat Atma Jaya University that has been with the lecturing schedule. To analyze the needs of parking space units, the Technical Implementation Guidelines for parking facilities issued by the Direktur Perhubungan Darat, was used The results of this study showed that for motor-cycle parking facilities, the space is inadequate at only 371.62 m2 or 52.40 % of the requirement is 709.20 m2 while the four-wheel drive is available for a large space is 1.616 m2or 135.77 % of the requirement is 1190.25 m2. Based on the results of this study is advisable for motor-cycle parking spaces for being added while for car parking spaces need to be a good arrangement.